RESILIENSI KOMUNITAS PETANI TIMUN APEL DALAM MENGHADAPI ANCAMAN KERAWANAN PANGAN (KASUS DESA TANJUNGPAKIS, KABUPATEN KARAWANG) - Siti Mariyani; Ekalia Yusiana; Zulfa Nur Auliatun Nissa; M. Mawardi J; Ana Melani (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2025)
Climate change affects the yield of timun apel plants, reducing the income of the timun apel farming community in Tanjung Pakis Village. The decline in income from timun apelproduction has resulted in the community's ability to meet food needs being disrupted, resulting in the threat of food insecurity. This research aims to determine the resilience of the apple-cucumber farming community in facing the threat of food insecurity due to climate change. This research was conducted using a case study method in the timun apel farming community in Tanjungpakis Village, Pakis Jaya District, Karawang Regency, because in this village, there is a community of timun apel farmers that has good natural resource potential, but there are ecological problems such as threats to production due to climate change. This research uses qualitative data with descriptive analysis. The research results show that the community of timun apel farmers in Tanjung Pakis Village already has reasonably good resources but still needs more adaptive capacity. Communities must utilize their resources as optimally as possible and increase adaptive capacity so that communities can be resilient in facing the threat of food insecurity due to climate change.